2019
DOI: 10.1111/sms.13555
|View full text |Cite
|
Sign up to set email alerts
|

Power output, cadence, and torque are similar between the forward standing and traditional sprint cycling positions

Abstract: Purpose: Compare power output, cadence, and torque in the seated, standing, and forward standing cycling sprint positions. Methods: On three separated occasions (ie, one for each position), 11 recreational male road cyclists performed a 14 seconds sprint before and directly after a high-intensity lead-up. Power output, cadence, and torque were measured during each sprint. Results: No significant differences in peak and mean power output were observed between the forward standing (1125.5 ± 48.5 W and 896.0 ± 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Standing while sprinting has a positive effect on power output when compared with a seated position (Bertucci et al, 2005;Bertucci et al, 2008;Merkes et al, 2020;Millet et al, 2002;Reiser et al, 2002;Rohsler et al, 2020). For example, Reiser and colleagues (Reiser et al, 2002) observed a 6 to 8% improvement in peak and mean power output while standing (19.4 and 11.0 W•kg-1, respectively) during a 30 s Wingate, compared with sitting (17.9 and 10.4 W•kg-1, respectively).…”
Section: Cyclist's Body Position During Road Cycling Sprintingmentioning
confidence: 99%
“…Standing while sprinting has a positive effect on power output when compared with a seated position (Bertucci et al, 2005;Bertucci et al, 2008;Merkes et al, 2020;Millet et al, 2002;Reiser et al, 2002;Rohsler et al, 2020). For example, Reiser and colleagues (Reiser et al, 2002) observed a 6 to 8% improvement in peak and mean power output while standing (19.4 and 11.0 W•kg-1, respectively) during a 30 s Wingate, compared with sitting (17.9 and 10.4 W•kg-1, respectively).…”
Section: Cyclist's Body Position During Road Cycling Sprintingmentioning
confidence: 99%
“…Scientists often measure a cyclist's maximal power on a traditional stationary ergometer (e.g. Reiser et al (2002); Dorel et al (2005); Gardner et al (2007); Hug et al (2011); Merkes et al (2020)). But unlike a bicycle, ergometers typically cannot lean from side-to-side.…”
Section: Introductionmentioning
confidence: 99%
“…The power output depends on the time course of the forces applied on the pedal, and these forces may be oriented in very different ways while producing the same torque output. Different positions, by changing saddle height or using different orientation of the trunk, could also lead to a similar output power [6].…”
Section: Introductionmentioning
confidence: 99%
“…The diverse environmental factors present in the field (e.g., terrain unevenness, wind speeds) may also affect the cycling performances [13,14]. Despite these limitations, laboratory testing has been proven to provide accurate modeling and evaluation of the cycling performance and may even allow for the prediction of competition scenarios [6,15,16].…”
Section: Introductionmentioning
confidence: 99%